Женщины в игре без правил: романы / Г. Н. Щербакова - Щербакова Галина Николаевна (Вагриус, 2007)
Экземпляры: ф.14 (2007) / Инвентарный номер: 51304 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Щ 61 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44